Pendampingan UMKM dalam Pemanfaatan Platform Digital untuk Branding dan Promosi Produk - Pratiwi, Endang; Astuti, Povi Tricahya; Reksi, Yulita; Stiawan, Evan; Hak, Nurul (Pakis Journal Institute, 2025)
The development of digital technology provides great opportunities for MSMEs to expand market reach and increase competitiveness through effective branding and promotion strategies. However, there are still many MSMEs that have not optimally utilized digital platforms. This study aims to examine the process and impact of MSME assistance in utilizing digital platforms for branding and product promotion purposes. Assistance activities are carried out through training, technical guidance, and intensive assistance that includes the use of social media, marketplaces, and the creation of digital content that is relevant to product characteristics. The approach used is a descriptive qualitative method with direct observation and interviews with the MSME actors involved. The results of the study showed that after receiving assistance, MSME actors experienced a significant increase in understanding digital marketing strategies, consistency in building brand identity, and increased interaction with consumers online. In addition, there was an increase in the number of sales and a wider range of promotions. Thus, targeted and sustainable assistance can encourage the digital transformation of MSMEs.